2023
DOI: 10.3390/medicina59010158
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implication of Small Dense LDL-Cholesterol Levels following Acute Coronary Syndrome

Abstract: Background and Objectives: Small dense LDL cholesterol is a strong risk factor for atherosclerosis. However, few studies have investigated the impacts of this specific lipid profile on the incident risk of adverse cardiovascular events in patients with acute coronary syndrome. Materials and Methods: Patients with acute coronary syndrome, who underwent revascularization, were included and followed for 2 years. The levels of small dense LDL cholesterol were measured at index discharge (day 0) in the setting of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The therapeutic target level for small dense LDL-cholesterol is another concern. A previous study suggested a cutoff of 20.9 mg/dL for secondary prevention in patients with acute coronary syndrome, [25] while another study proposed a cutoff of 32.6 mg/dL in a similar cohort [26]. The median value of small dense LDL-cholesterol in our study was 38.8 mg/dL.…”
Section: Impact Of Pemafibrate On Reducing Cardiovascular Eventssupporting
confidence: 50%
“…The therapeutic target level for small dense LDL-cholesterol is another concern. A previous study suggested a cutoff of 20.9 mg/dL for secondary prevention in patients with acute coronary syndrome, [25] while another study proposed a cutoff of 32.6 mg/dL in a similar cohort [26]. The median value of small dense LDL-cholesterol in our study was 38.8 mg/dL.…”
Section: Impact Of Pemafibrate On Reducing Cardiovascular Eventssupporting
confidence: 50%
“…8) We have further demonstrated its validity in another clinically important scenario, acute coronary syndrome, where small dense LDL-cholesterol levels may provide an additional tool for risk stratification. [9][10][11] Predictability was not affected by the presence of baseline statin use. Given the lack of an on-label measurement of small dense LDL-cholesterol levels, the Sampson equation may be a feasible method to measure and track in patients presenting with acute coronary syndrome.…”
Section: Clinical Implication Of the Sampson Equationmentioning
confidence: 86%
“…Several cutoff values for small dense LDL-cholesterol have been proposed to predict clinical outcomes after acute coronary syndrome. [9][10][11] In patients at a high baseline risk of adverse cardiovascular events, incorporating the measurement of small dense LDL particles should be considered by practitioners as an additional risk modifier when making clinical decisions about lipidlowering therapies. A high proportion of patients may not have exceedingly unacceptable LDL-cholesterol levels but instead have a higher percentage of small dense LDLcholesterol, for which further intensification of therapies should be considered.…”
Section: Clinical Implication Of the Sampson Equationmentioning
confidence: 99%
See 1 more Smart Citation